National cultural characteristics as defined by Hofstede's dimensions and their associations with population health - Zidkova, Radka; Furstova, Jana; Malinakova, Klara; van Dijk, Jitse P; Tavel, Peter; Gulis, Gabriel (BMC public health, 2025)
BACKGROUND: Understanding population health trends and their key determinants is essential for planning health services and implementing effective interventions. One of these determinants may be national cultural characteristics that are related to various health outcomes and health-related behaviours. However, little is known about their potential association to overall burden of disease. Thus, this study examined whether cultural characteristics expressed by Hofstede indexes are associated with the burden of disease. METHODS: We used data from open-source databases - Hofstede's Cultural Index, the Global Burden of Diseases (GBD) and the Human Development Index (HDI). The final sample comprised 69 countries covering all the continents. The burden of disease was measured using disability-adjusted life years (DALYs), years lived with disabilities (YLD), and years of life lost (YLL). National cultural characteristics were measured using Hofstede's dimensions. Bayesian correlation analyses were conducted to assess the relationships between cultural dimensions and health outcomes, stratified by countries' HDI levels. RESULTS: In countries with a very high HDI, there was strong evidence (Bayes Factor > 10) of a positive correlation of Power distance with the total disability-adjusted life years (r = 0.448) and years of life lost (r = 0.528), and Individualism (r = 0.667) and Indulgence (r = 0.494) with years lived with disabilities. In contrast, Long-term orientation negatively correlated of with years lived with disabilities (r = -0.527) and Indulgence with disability-adjusted life years (r = -0.437) and years of life lost (r = -0.537). Further, Power distance and Indulgence were correlated with the majority of the GBD indicators and Individualism with a few GBD indicators. In countries with a high and medium HDI, strong evidence of the associations was found in only a few cases. CONCLUSION: We found a correlation between national cultural characteristics and burden of disease. Policy-makers should consider integrating cultural factors into public health strategies to better align healthcare interventions with the local population's values and behaviours. Moreover, cross-cultural research and collaboration should increase to understand how cultural influences can be used to mitigate disease burdens and improve health outcomes globally. This study also opens a potentially new research area within population health research.
Keywords: Hofstede’s index; Burden of disease; Cultural characteristics; Bayesova věta; Population health; zdravotní stav populace; Global Burden of Disease; Disability-Adjusted Life Years; Cultural Characteristics; lidé; kulturní charakteristiky; Bayes Theorem; Cost of Illness; počet let života s onemocněním; osobní újma zaviněná nemocí; Humans; Population Health; globální zátěž nemocemi